Dried noodles with red bean flour substitution (Vigna angularis): Low glycemic index food alternative - Imansari, Adillah; Siauta, Viere Allanled; Mentari, Ratna; Pettalolo, Sri Rezeki (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2026)
ABSTRAK  Latar Belakang: Rekomendasi asupan diet pada penderita Diabetes Melitus yang perlu diperhatikan yaitu mengkonsumsi makanan yang mengandung indeks glikemik (IG) rendah. Mie kering dengan subtitusi tepung kacang merah dapat menjadi pilihan dalam menu makanan penderita DM.  Tujuan: Penelitian ini bertujuan untuk menganalisis uji daya terima, kandungan gizi dan indeks glikemik (IG) pada formulasi mie kering dengan subtitusi tepung kacang merah.  Metode: Penelitian adalah eksperimen dengan 3 perlakuan formula mie kering substitusi tepung terigu dan kacang merah (F1 = 80%: 20%; F2 = 60%;40%; F3 = 40%:60%). Data yang dikumpulkan yaitu uji daya terima menggunakan uji hedonik pada 30 responden dan uji kandungan gizi menggunakan analisis uji proksimat yang kemudian dianalisis untuk menentukan formulasi terbaik dengan analisis ANOVA. Analisis nilai indeks glikemik pada 9 responden dengan metode IAUC.  Hasil: Mie kering substitusi tepung kacang merah berpengaruh signifikan pada hasil uji daya terima (warna, dan tekstur) dan kandungan gizi makro (protein, lemak) (p<0,005). Formulasi terbaik adalah F1 dengan subtitusi tepung kacang merah 20% dengan nilai IG = 42,08%. Kesimpulan: Mie dengan subtitusi 20% tepung kacang merah memiliki indeks glikemik yang termasuk dalam golongan rendah, yaitu 42,08%. ABSTRACT Background: Dietary recommendations for Diabetes Mellitus patients are consuming foods with a low glycemic index (GI). According to the results, dried noodles substituted with red bean flour is one of the foods recommended, considering the high protein and fiber content of red beans which are classified as low GI foods.  Objective: This study aimed to analyze the acceptability, nutritional content, and glycemic index (GI) of dried noodle formulations with red bean flour substitution.  Methods: This was an experimental study with 3 treatments of dried noodle formulations substituting wheat flour and red beans (F1 = 80%: 20%; F2 = 60%; 40%; F3 = 40%: 60%). The data collected were acceptability tests using hedonic tests on 30 respondents and nutrient content tests (carbohydrates, protein, and fat content) utilizing proximate analysis which was then analyzed to determine the best formulation using Analysis of Variance (ANOVA). Analysis of the glycemic index in 9 respondents using the IAUC method.  Results: Dried noodles with red bean flour substitution had a significant effect on the results of the acceptability test (color and texture) and macronutrient content (protein, fat) (p <0.005). The best formulation was F1 with 20% red bean flour substitution with a GI value of 42.08%.  Conclusion: Dried noodles with 20% red bean flour substitution have a glycemic index  classified as low, specifically 42.08%.